Early childhood malnutrition impairs adult resting brain function using near-infrared spectroscopy - Roger, Kassandra; Vannasing, Phetsamone; Tremblay, Julie; Bringas Vega, Maria L.; Bryce, Cyralene P.; Rabinowitz, Arielle; Valdes-Sosa, Pedro Antonio; Galler, Janina R.; Gallagher, Anne (Frontiers in Human Neuroscience, 2024)
Early childhood malnutrition affects 200+ million children under five years of age worldwide and is associated with persistent cognitive, behavioral and psychiatric impairments in adulthood. However, very few studies have investigated the long-term effects of childhood protein energy malnutrition (PEM) on brain function using a functional hemodynamic brain imaging technique. This study aims to investigate functional brain network alterations using Near Infrared Spectroscopy (NIRS) in adults, aged 45-51 years, from the Barbados Nutrition Study (BNS) who suffered from a single episode of malnutrition restricted to their first year of life (n=26) and controls (n=29). A total of 55 individuals from the BNS cohort underwent NIRS recording at rest. Using functional connectivity and permutation analysis, we found patterns of increased Pearson's correlation with a specific vulnerability of the frontal cortex in the PEM group (ps <0.05). Using a graph theoretical approach, mixed ANCOVAs showed increased segregation (ps=0.0303 and 0.0441) and decreased integration (p=0.0498) in previously malnourished participants compared to healthy controls. These results can be interpreted as a compensatory mechanism to preserve cognitive functions, that could also be related to premature or pathological brain aging. To our knowledge, this study is the first NIRS neuroimaging study revealing brain function alterations in middle adulthood following early childhood malnutrition limited to the first year of life.